KEWENANGAN MAHKAMAH KONSTITUSI DALAM PENYELESAIAN SENGKETA HASIL PILKADA PASCA PUTUSAN NOMOR 85/PUU-XX/2022 - Muhammad Didid; Ahmad rustan; Fahmi Jambak (Jurnal Hukum to-ra : Hukum untuk mengatur dan melindungi masyarakat, 2026)
Constitutional Court Decision Number 85/PUU-XX/2022 reaffirmed the Constitutional Court's (MK) authority to examine and resolve disputes over regional head election (Pilkada) results, despite the absence of a special election court. This decision sparked debate regarding the limits of the Constitutional Court's authority and its implications for the principles of separation of powers and legal certainty. This study aims to analyze the construction of the Constitutional Court's authority following Decision Number 85/PUU-XX/2022 and its implications for the Pilkada dispute resolution system in Indonesia. The research method used is normative legal research with a statutory approach, a case approach, and a conceptual approach. The results show that Decision Number 85/PUU-XX/2022 strengthens the Constitutional Court's role as guardian of the constitution, but also demonstrates a tendency to expand its authority, potentially giving rise to problems of legal certainty and the risk of judicial overreach. The novelty of this research lies in its critical analysis of the shifting role of the Constitutional Court in the post-2022 Pilkada regime and its proposed strengthening of the institutional design for a more constitutional Pilkada dispute resolution..